Safeguards at a glance: Supporting the rights of Indigenous Peoples and local communities in REDD+ and other forest-based initiatives - Sarmiento Barletti, J.P.; Larson, A.M.; Lofts, K.; Frechette, A. (Center for International Forestry Research, 2021)
Pledges for new investment in tropical forests may support sustainable development objectives, but also pose risks to forest-dependent communities. We compared nine criteria to understand differences across standards and guidelines, focusing on their engagement with the rights of the IPLCs that steward the forests where REDD+ is implemented. There is considerable variation in how safeguard standards and guidelines engage with the rights of IPLCs.